Level of motor skill development of preschool students - Abdullah, Borhannudin; Abd Aziz, Wan Azira; Yusof, Aminuddin (Editura Universitatea din Pitesti, 2016)
Purpose: The research aims to identify the level of motor skill development among preschool students in Putrajaya. Methodology: The ex post facto research involves 120 six year old preschool children (60 males and 60 females) using Ulrich motor skill assessment (Ulrich, 2000) to measure locomotor and ability to control object. based on the Gross Motor Development Quotient (GMDQ) scores. The scores were furthered analyzed using ANOVA to compare differences in motor performances of preschool students among various preschool centers. Result: The findings showed significant differences in GMDQ scores [F (2,117) = 7.8, p< 05] between government and private students compared to KEMAS preschools students. The age equivalence locomotors score (AEL) with age equivalence measure (AEM) showed a significant difference between government preschoolers with private preschoolers for AEL [F (2,117) =3.41, p< 0.05] and AEM [F (2,117) =7.39, p< 0.05] and KEMAS preschoolers. Findings and discussion: In term of motor skills development among children in the government, private and KEMAS preschools, results showed children in private preschools scored the highest with KEMAS preschools scored highest for AEM. The results also showed a delay in mastering both locomotors (5 to 8 months delay) and controlling objects (10 to 19 months delay) skill among preschool children. The research suggests knowledge of identifying gross motor skills of preschool children needs to be included in preschool teacher’s training curriculum. At the same time, more comprehensive and systematic physical activities should be designed according to the age equivalent to ensure better locomotor development among preschool children regardless where they are either in the government or private preschool centers.